Application of different methods used to measure the apparent diffusion coefficient of renal cell carcinoma on the same lesion and its correlation with ISUP nuclear grading - Kilicarslan, Gulhan; Eroglu, Yesim; Kilicarslan, Ahmet (Springer, 2022)
Purpose To determine the most frequently used different apparent diffusion coefficient (ADC) measurement methods in renal cell carcinoma (RCC), and their correlation with the International Society of Urological Pathology (ISUP) histologic grading system. Methods A total of 99 patients who underwent diffusion-weighted imaging and whose pathologic diagnosis of RCC was confirmed were included in the study. As a result of a literature review, region of interest (ROI) selection and measurement methods were determined in five ways. These included a small ROI (ADC1) on the solid part of the lesion showing the most restriction; a large ROI (ADC2) on the solid part of the lesion showing restriction; ROI (ADC3) that covered the lesion in the cross-section with the largest diameter, which was obtained by placing ROIs (ADC4) covering the lesion on all sections of the lesion; three small ROIs (ADC5) on solid parts of the lesion showing the most restriction. Then, ADC measurements were made from the contralateral normal kidney parenchyma. Tumors were pathologically subdivided [71 clear cell RCCs (ccRCC), 17 chromophobe RCCs (chRCC), 11 papillary RCCs (pRCC)], and graded according to the ISUP nuclear grading system (42 high-grade, 57 low-grade). Data were analyzed statistically. Results In all measurement methods, ADC values of RCCs were statistically significantly lower than normal kidney ADC values. There were no differences between the ADC3 and ADC4 measurements of RCCs (p = 0.999). There was a statistical difference in other measurement methods (p < 0.001). There were differences between ccRCCs and pRCCs and chRCCs in all measurement methods. In all measurement methods, pRCC and chRCC ADC values were lower than ccRCC ADC values. When ISUP nuclear grading and ADC values were compared, there was a statistically inverse correlation between all ADC measurements. The strongest correlation was found in the ADC1 and ADC5 measurements. When the ADC values of ISUP low and high-grade groups were compared, a significant difference was found in the ADC5 measurement method (p = 0.046). Conclusion According to the findings of the study, ADC5 is the measurement method that shows the best correlation with the ISUP histologic grading system. Therefore, we think that ADC5 can be the primary measurement method for determining the ADC value of RCCs. [GRAPHICS] .
Keywords: Renal cell carcinoma; ADC; Diffusion-weighted imaging; Nuclear grading; ISUP